Treating venous ulcers: reality in Brazil and Portugal - Daniel Silveira da Silva; Giselda Veronice Hahn (Universidade Federal de Santa Maria, 2012)
Objective: to describe resources nurses in the public health in the treatment for venous ulcers used in two different social and economic realities. Method: exploratory descriptive field study with qualitative approach. Data were collected through a semi-structured questionnaire. The sample included six nurses from every town. Content analysis was done. Results: we have found out that some topic agents were used in both studied towns, but in Leiria there is a much wider variety of recourses. Conclusions: there is no adequate covering for all wounds, due to the specificities for every type or phase of lesion. Nurses have to know and check new technologies and recourses available in the market, and investigate its practices to heighten the arguing powers in with managers and other health team workers. It is necessary to make an interdisciplinary evaluation of the patient and including him/her in the therapeutic plan, especially in cases of chronic wounds